Dialogic Reading in Intensive Reading Lessons: Indonesian Secondary EFL Teachers’ Perspectives - Haris Praditya Wijaya; Silfia Asning Tias; Soe Soe Win (New Language Dimensions, 2026)
Intensive reading in Indonesian secondary EFL classrooms is often shaped by teacher-centered instruction, literal comprehension tasks, and examination-oriented practices. These conditions may limit students’ opportunities to engage critically and personally with texts. This qualitative descriptive study investigated how nine senior high school English teachers in Surabaya perceived and planned Dialogic Reading strategies in intensive reading lessons. Data were collected through semi-structured interviews and instructional portfolio analysis, including lesson plans and teaching modules. The data were analyzed through data condensation, data display, and conclusion drawing. The study was informed by Rosenblatt’s Transactional Theory and Whitehurst’s Dialogic Reading framework, particularly the CROWD prompts and PEER sequence. The findings indicate that several teachers attempted to move from an efferent, text-centered reading orientation toward a more transactional approach. Distancing, open-ended, and Wh-prompts were used to connect texts with students’ sociocultural experiences, while non-judgmental evaluation and peer expansion supported safer classroom interaction. The study suggests that Dialogic Reading can provide a low-resource pedagogical framework for making intensive reading more interactive, contextual, and emotionally supportive in Indonesian secondary EFL classrooms.